Fantasies of Identification : Disability, Gender, Race - Samuels, Ellen Jean (Book collections on Project MUSE., 2014)
"In the mid-nineteenth-century United States, as it became increasingly difficult to distinguish between bodies understood as black, white, or Indian; able-bodied or disabled; and male or female, intense efforts emerged to define these identities as biologically distinct and scientifically verifiable in a literally marked body. Combining literary analysis, legal history, and visual culture, Ellen Samuels traces the evolution of the "fantasy of identification"--The powerful belief that embodied social identities are fixed, verifiable, and visible through modern science. From birthmarks and fingerprints to blood quantum and DNA, she examines how this fantasy has circulated between cultural representations, law, science, and policy to become one of the most powerfully institutionalized ideologies of modern society."--Provided by publisher.